Integration of AI, Big Data, and Cultural Heritage in Tourism Marketing: A Case Study of Klaten - Eneng Nuraeni; Wahyu Purnomo; Indra Iryanto Nur Hidayat (International Journal of Economic and Tourism Research, 2025)
This study investigates the use of artificial intelligence, big data, and cultural heritage in tourism marketing in Klaten Regency. The study looks at how AI-driven customisation, data analytics, and cultural authenticity help to boost tourist engagement and destination competitiveness. The study uses qualitative methodologies, including interviews with tourism stakeholders and content analysis, to identify significant themes such as AI-driven recommendation systems, data-driven decision-making, and cultural storytelling. The findings indicate that AI-powered solutions considerably improve consumer experiences, and Big Data analytics boost strategic planning and market segmentation. Furthermore, cultural heritage remains an important aspect in attracting tourists, with digital storytelling and immersive technology helping to preserve and promote Klaten's cultural treasures. AI-powered interactive experiences, such as augmented reality (AR) and virtual reality (VR), enhance visitor engagement, making cultural institutions more accessible and desirable. The study emphasizes the importance of predictive analytics in studying visitor behavior and customizing marketing techniques to enhance destination branding. Despite these benefits, issues such as technology infrastructure, data protection concerns, and the digital gap between enterprises remain. Addressing these issues needs collaboration among local governments, tourist stakeholders, and technology suppliers to promote inclusive and ethical AI deployment. The study has theoretical and managerial implications, underlining the importance of sustainable digital strategy and responsible AI implementation. Future research should focus on building AI-powered smart tourism ecosystems in order to promote ethical and culturally sensitive tourist development.